1999
DOI: 10.1097/00006123-199901000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Severe Cerebral Vasospasm in Three Patients after Aneurysmal Subarachnoid Hemorrhage: Initial Observations Regarding the Use of Intraventricular Sodium Nitroprusside in Humans

Abstract: These preliminary observations suggest that sodium nitroprusside delivered by an intrathecal route of administration may be a useful treatment for severe vasospasm complicating SAH in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 11 publications
3
48
0
Order By: Relevance
“…those that are not covered by the clot) to further dilate, resulting in the 'steal syndrome' 4,68 . None of these issues has been properly addressed either experimentally or clinically and both a beneficial effect 19,97,98,112 and failure to improve cerebral vasospasm were reported with NO donors administrated via these routes 79 .…”
Section: No Delivery: Localmentioning
confidence: 99%
“…those that are not covered by the clot) to further dilate, resulting in the 'steal syndrome' 4,68 . None of these issues has been properly addressed either experimentally or clinically and both a beneficial effect 19,97,98,112 and failure to improve cerebral vasospasm were reported with NO donors administrated via these routes 79 .…”
Section: No Delivery: Localmentioning
confidence: 99%
“…In the case of aneurysmal SAH, local administration is delivering NO donors intrathecally or intraventricularly 19,79,97,98,112 . Such a route can avoid many disadvantages of systemic administration.…”
Section: No Delivery: Localmentioning
confidence: 99%
“…NO influence on blood flow 11,15,99,106,113 , disappearance of neuronal nitric oxide synthase (nNOS) immunoreactivity from the arteries in spasm 75 , endothelial nitric oxide synthase (eNOS) dysfunction in cerebral vessels after SAH 37 , decreased levels of nitrite in the cerebrospinal fluid (CSF) during vasospasm development 40,70,76 , as well NO affinity for the heme moiety 52 together, strongly suggest that decreased availability of NO in the cerebral arterial wall after SAH is responsible for delayed cerebral vasospasm 70 . Recent research has significantly advanced our understanding of the NO-related pathophysiologic changes in the cerebral arteries leading to vasospasm and introduced new possibilities for NO-based therapy for vasospasm 23,76,98 .…”
Section: Introductionmentioning
confidence: 99%
“…3) A clinical trial with intrathecal sodium nitroprusside observed good vasorelaxation without significant reduction of mean arterial pressure. 23) However, the feasibility of continuous use remains unclear, as cyanide poisoning and cyanide encephalopathy are possible, even at low doses. 21) Higher doses of intravenous nitroglycerin are necessary for the treatment of cerebral vasospasm, which may affect mean arterial pressure.…”
Section: Discussionmentioning
confidence: 99%